Faktor Penyebab Kecemasan Matematika (Mathematics Anxiety) dalam Belajar Matematika: Systematic Literatur Review - Marweli, Marweli; Meiliasari, Meiliasari (Supermat : Jurnal Pendidikan Matematika, 2024)
In mathematics learning, many factors affect concentration and interest in learning, including anxiety experienced by students. Mathematics anxiety is a feeling of worry and discomfort when doing activities related to mathematics. For this reason, this study aims to identify the factors that cause mathematics anxiety and efforts to overcome mathematics anxiety. The method used in this study is SLR (Systematic Literature Review). Data was collected through documentation and review of 14 journals obtained from Google Scholar. The journals analyzed were published in the last five years, from 2019 to 2024. From the overall analysis in this study, five factors influence anxiety: environmental, intellectual, mental, personality, and individual factors. The impact of anxiety that arises greatly affects the learning process so that the final results in student learning always feel very bad, with the learning outcomes obtained being lower. Efforts that can reduce mathematics anxiety can be grouped to create more conducive lessons, namely, teaching mathematics with various methods that accommodate students' learning styles, not emphasizing memorization in the mathematics learning process, and creating a fun and comfortable mathematics classroom atmosphere.